ON THE SKILLFUL DESCRIPTION OF EVENTS RELATED TO THE KHIVA KHANATE OF THE 19TH CENTURY IN THE HISTORICAL WORK OF MUHAMMADRIZA AGAKHI “SHAHID UL-IKBAL” (TAMADDUN NURI JURNALI, 2025)
The article presents information about skilful description of events related to the Khiva Khanate of the XIX century in the historical work ‘Shahidu-l-ikbal’ by Muhammad Riza Agahi.